Effects of Cabergoline and Levetiracetam on the Histological and Stereological Structure of the Cerebral Cortex, Hippocampus and Cerebellum of Rats With Pentylenetetrazol-Induced Seizure - Mohammad Hossein Hajati Pishvari; Yousef Panahi; Gholamreza Hamidian (مجله دانشگاه علوم پزشکی گیلان)
Background: Epilepcy is a chronic neurological disease, and due to its complex mechanism, the current therapeutic drugs for it are not effective enough. It may have a non-neurological origin such as astrocytes and microglia. Objective This study aims to investigate the effect of cabergoline and levetiracetam (alone or combined) on the histological and stereological structure of the cerebral cortex, hippocampus, and cerebellum in rats with pentylenetetrazol (PTZ)-induced seizure. Methods: In this experimental study, samples were 30 female rats in five groups of control, seizure (PTZ-induced kindling), seizure+levetiracetam, seizure+cabergoline, seizure+levetiracetam+cabergoline. Levetiracetam and cabergoline were used at 50 and 0.05 mg/kg doses, respectively, and half of these doses were used in the seizure+levetiracetam+cabergoline group. After anesthesia, animals’ brain tissue was removed and after preparing tissue slices, the number of neurons and neuroglia was examined using stereology technique. Results: In the cerebral cortex and in the molecular and granular layers of the cerebellum, the numbers of neurons and neuroglia in the treatment groups were not significantly different from those in the control group, but a significant decrease was observed in the CA1, CA2, and CA3 regions of the hippocampus in the seizure group compared to the control group. In dentate gyrus, the number of neurons in all treatment groups and the number of neuroglia in the seizure group showed a significant decrease compared to the control group. In the Purkinje layer of the cerebellum, there was no significant change in the number of neurons compared to that in the control group. Conclusion: The hippocampus is more involved in the occurrence of seizure activity than other parts of the brain. Neurons and neuroglia play an essential role in seizures, but more studies are needed for determining the relationship between the number of these cells and the use of cabergoline because their number decreases in different parts of the hippocampus following chronic seizures, where the relationship is different between dendrite gyrus and CA regions.